A new algorithm for the fast and stable identification of FAY coefficients and its application as a universal platform for yield surface modeling. (15th December 2020) - Manopulo, Niko; Carleer, Bart
Abstract: A new approach is proposed for enabling the exchange and testing of arbitrary yield surface models, solely based on a set of Fourier coefficients. This effectively reduces the implementation efforts to a single generic model description. The proposed method exploits the Fast Fourier Transform algorithm to identify a unique set of coefficients of the FAY model based on any plane stress yield surface model. The approach is tested based on well-known yield functions and is analyzed with respect to accuracy and convexity. Finally a universal yield surface format is proposed for exchanging FAY coefficients in scientific and technical communities.